RESONANT (P plus RES) CONTROLLER APPLIED TO VOLTAGE SOURCE INVERTER WITH MINIMUM DC LINK CAPACITOR - Gazoli, Jonas Rafael; Oliveira F, Milton Evangelista de; Espindola, Marcos Fernando; Siqueira, Thais Gama de; Villalva, Marcelo Gradella [UNESP]; Ruppert, Ernesto; IEEE (Ieee, 2011)
Voltage source inverters use large electrolytic capacitors in order to decouple the energy between the utility and the load, keeping the DC link voltage constant. Decreasing the capacitance reduces the distortion in the inverter input current but this also affects the load with low-order harmonics and generate disturbances at the input voltage. This paper applies the P+RES controller to solve the challenge of regulating the output current by means of controlling the magnitude of the current space vector, keeping it constant thus rejecting harmonic disturbances that would otherwise propagate to the load. This work presents a discussion of the switching and control strategy.
Keywords: current control; reduced dc link capacitor; p plus res; resonant controller; space vector; voltage source inverter